2020
DOI: 10.1097/txd.0000000000000970
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Cohort Analysis After Liver Transplantation Shows de Novo Extended Release Tacrolimus Is Safe, Efficacious, and Minimizes Renal Dysfunction

Abstract: Background. The use of once-daily extended-release tacrolimus (ERT) is associated with improved long-term graft and patient survival when compared with twice-daily tacrolimus (BDT), but the underlying reasons for differential survival are unclear. The aim of the study was to compare clinical outcomes known to impact on posttransplant survival for de novo BDT and ERT in liver transplantation (LT) recipients. Methods. We conducted a single-center, prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…When information was available, ≥78.1% of patients were White; the exception was Chauhan et al, in which 36.3–43.3% of patients across study arms were White [ 20 ]. The primary diseases at baseline varied between studies and study arms ( Table 4 ), but included alcoholism or ethanol abuse (23.1–71.4% across 3 studies [ 23 , 24 , 29 ]) hepatitis C virus infection (0–41.8% in 11 studies [ 7 , 19 , 20 , 22 26 , 28 30 ]), and hepatocellular carcinoma (2.3–63.6% in 10 studies [ 7 , 19 22 , 24 , 27 30 ]).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…When information was available, ≥78.1% of patients were White; the exception was Chauhan et al, in which 36.3–43.3% of patients across study arms were White [ 20 ]. The primary diseases at baseline varied between studies and study arms ( Table 4 ), but included alcoholism or ethanol abuse (23.1–71.4% across 3 studies [ 23 , 24 , 29 ]) hepatitis C virus infection (0–41.8% in 11 studies [ 7 , 19 , 20 , 22 26 , 28 30 ]), and hepatocellular carcinoma (2.3–63.6% in 10 studies [ 7 , 19 22 , 24 , 27 30 ]).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Mean GFR/eGFR decreased numerically over time in at least 1 study arm from 6 publications where data were reported according to study arm [ 19 , 22 24 , 26 , 27 ]. Where mean data were available, eGFR ranged from 71.4 to 119.6 mL/min/1.73 m 2 (means within CKD stage 2 to stage 1) across studies at baseline, from 76.0 to 85.2 mL/min/1.73 m 2 (CKD stage 2) at 6 months [ 22 , 26 , 27 ], and was 77.2 and 79.1 mL/min/1.73 m 2 (CKD stage 2) in 2 studies at 12 months [ 24 , 26 ].…”
Section: Renal Functionmentioning
confidence: 99%
See 3 more Smart Citations